Dispositions of subsisting equitable interests and section 53(1)(c) of the Law of Property Act 1925 - English, J; Atmaz Al-Sibaie, J (Sweet and Maxwell, 2024)
Highlights issues commonly arising with the application of the Law of Property Act 1925 s.53(1)(c) concerning the disposition of subsisting equitable interests, notably the meaning of "disposition" and the nature of equitable interests and transactions involving them. Argues that the decision in Grey v Inland Revenue Commissioners (HL) with its broad definition of "disposition" has led to confusion and was wrongly decided.